Enhancing Mandarin Learning Through Task-Based Activities: A Situated Learning Approach in Real-World Contexts - Mok Soon Sim (Universitas Negeri Malang, 2025)
This study explores how non-native Mandarin learners apply situated learning theory in authentic contexts through interactions with native speakers in the Malaysian Chinese community. Adopting a qualitative case study approach, 30 students from a beginner-level Chinese class at a public university were selected, and their recorded conversations and transcribed texts were analyzed. The research is framed within Lave & Wenger's (1991) situated learning theory and Ellis's (2009) task-based teaching framework. Key findings include: (1) Task-based learning enhances linguistic authenticity; (2) Communicative tasks facilitate social interaction; (3) The constructivist approach reduces reliance on traditional instruction. These findings provide valuable pedagogical insights for Mandarin instructors, contributing to improvements in teaching methodologies, task design, and curriculum development, ultimately increasing overall teaching effectiveness.